2006
DOI: 10.1007/s00253-005-0237-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vitreoscilla hemoglobin enhances growth and levels of α-amylase in Schwanniomyces occidentalis

Abstract: A metabolic engineering approach was exploited to improve growth and protein secretion in the non-conventional yeast, Schwanniomyces occidentalis. Vitreoscilla hemoglobin (VHb) gene was expressed in S. occidentalis under the control of the native alpha-amylase (AMY1) promoter. Expression of VHb was confirmed by reverse transcriptase polymerase chain reaction and Western blot hybridization analysis. Effect of VHb on growth and protein secretion was studied in synthetic medium under both limiting and non-limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
4
20
0
2
Order By: Relevance
“…As P vgb is not functional in most gram-positive bacteria or eukaryotic organisms, various promoter strategies have been adopted by researchers to induce expression of VHb in heterologous hosts. Suthar et al [18] used an α-amylase promoter P AMY1 in Schwanniomyces occidentalis; Horng et al [22] applied P BAD in E. coli; Feng et al [20] used P luxs in Bacillus thuringiensis; and Xiong et al [16] employed P dsz in Rhodococcus erythropolis. In this study, the first and second codons of vgb were mutated to GTG and CTG respectively by site-directed mutagenesis and SOE-PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As P vgb is not functional in most gram-positive bacteria or eukaryotic organisms, various promoter strategies have been adopted by researchers to induce expression of VHb in heterologous hosts. Suthar et al [18] used an α-amylase promoter P AMY1 in Schwanniomyces occidentalis; Horng et al [22] applied P BAD in E. coli; Feng et al [20] used P luxs in Bacillus thuringiensis; and Xiong et al [16] employed P dsz in Rhodococcus erythropolis. In this study, the first and second codons of vgb were mutated to GTG and CTG respectively by site-directed mutagenesis and SOE-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…VHb has become a versatile tool in high-density fermentation of micro-organisms susceptible to oxygen supply [10,11]. Recent studies of VHb applications include: (i) promoting the biosyntheses of biochemical precursors (such as Dihydroxyacetone) [1215]; (ii) improving bioremediation (improving desulfidations in Rhodococcus erythropolis) [16]; (iii) enhancing the production of important enzymes (such as D-amino acid oxidase) [17,18]; (iv) improving the biosyntheses of antibiotics and biopesticides [19,20], and (v) promoting the production of biopolymer materials (such as poly-γ-glutamic acid) [21,22].…”
mentioning
confidence: 99%
“…In most cases bacteria have been used as the host cells. Enzymes for which production has been increased include D-amino oxidase (an increase of about 90%; Yu et al 2008), L-asparaginase (an increase of up to 70%;Geckil et al 2006), and a-amylase (3-fold increase; Suthar and Chattoo 2006). Production of mussel adhesive protein (90% increase; Kim et al 2008) and Bacillus thuringiensis Li et al 2010).…”
Section: Production Of Proteins and Other Biochemicalsmentioning
confidence: 97%
“…It has been reported that the overexpression of the gene encoding a bacterial hemoglobin from Vitreoscilla in Acremonium chrysogenum or in A. niger leads to a relief of stress when the transformants were exposed to oxygen limitation [44,45]. These hemoglobin proteins enhanced the production of alpha-amylase by the yeast Schwanniomyces occidentalis [46]. CPPs may produce a similar effect by increasing the concentration of the endogenous A. awamori hemoglobin-like protein.…”
Section: Discussionmentioning
confidence: 99%